Perturbed dynamics of discrete-time switched nonlinear systems with delays and uncertainties. (May 2016) - Liu, Xingwen; Cheng, Jun
Abstract: This paper addresses the dynamics of a class of discrete-time switched nonlinear systems with time-varying delays and uncertainties and subject to perturbations. It is assumed that the nominal switched nonlinear system is robustly uniformly exponentially stable. It is revealed that there exists a maximal Lipschitz constant, if perturbation satisfies a Lipschitz condition with any Lipschitz constant less than the maximum, then the perturbed system can preserve the stability property of the nominal system. In situations where the perturbations are known, it is proved that there exists an upper bound of coefficient such that the perturbed system remains exponentially stable provided that the perturbation is scaled by any coefficient bounded by the upper bound. A numerical example is provided to illustrate the proposed theoretical results. Abstract : Highlights: There is a Lipschitz constant with which the stability property can be preserved. A bound of perturbation exists to make perturbed system being exponentially stable. A novel non-Lyapunov approach is used in the analysis.